Radical Consequences of Benign Neglect: The Rise of the PKK in Germany - Eccarius-Kelly, Vera (Tufts Archival Research Center, 2005)
Volume 24, Issue 1. Spring German political circles have minimized growing inter-ethnic hostilities between Turkish and Kurdish immigrants, refusing to entangle the country in the Kurdish struggle for independence. But Germanyï¿½s strategy of benign neglect is beginning to backfire.